A review of techniques for characterising scoria cone morphologies - Bailey, Ryan; Varley, Nick; Blackett, Matthew (Frontiers in Earth Science, 2025)
Scoria cones represent the most abundant volcanic landforms on Earth, commonly formed by mafic eruptions that produce scoria and lava during short-lived, low-volume events. Their morphology exhibits considerable variability, influenced by eruption style, tectonic setting, and post-emplacement modification. Morphometric analysis of scoria cones is critical for understanding magmatic system evolution, eruptive processes, tectonic controls, age estimation, erosional history, climate influences, hazard assessment, and paleo-reconstruction. Early studies relied on manual topographic measurements and formula-based methods to reconstruct cone geometry, but these approaches are highly sensitive to irregular morphologies and subjective parameter selection. The advent of satellite imagery, high-resolution Digital Elevation Models (DEMs), and semi-automated algorithms has revolutionised scoria cone analysis, enabling more precise and reproducible morphometric characterisations. Despite these advancements, persistent inconsistencies arise from differences in DEM resolution, cone boundary identification, and methodological choice, each contributing to uncertainty in results. The lack of a standardised methodological framework hampers direct comparison between studies and limits the reliability of derived parameters. This review synthesises current methodologies and datasets for scoria cone morphometry across diverse geomorphological, tectonic, and volcanic environments, aiming to clarify the strengths and limitations of each approach and to guide future research toward best practices in scoria cone analysis.